The assessment of risk tolerance of Hungarian travellers towards abroad trips - Solyomfi, Andrea Hanna; Skačkauskienė, Ilona; Borisov, Igor; Vinogradov, Szergej (Journal of Business Economics and Management, 2024)
This study identified and examined significant factors affecting the risk tolerance of Hungarian travellers towards abroad trips. Data for the empirical research was derived from an online survey. The final questionnaire included 45 statements describing aspects of travel safety and travel preferences. There was a total of 496 responses, which enabled them to be analyzed. A structural equation modeling (SEM) approach was used to develop the model of risk tolerance assessment. As a result of the study, physical security, price sensitivity, mood-driven factor, and destination’s image in the media may be considered as substitutes for determining travellers’ risk tolerance. This research contributes to the body of knowledge by supporting the proposition that inner personality traits and image factors may influence tourism preferences, suggesting future studies should use a multivariate approach to explain and predict tourism choices. Tourism managers and private companies operating in this sector can find the results of this study very helpful in planning and promoting tourism to risky destinations.